(untitled) (Research, Society and Development, 2025)
Introduction: Meditation is an integrative practice that reduces stress, anxiety, and depression, common mental health issues among healthcare workers. This practice enhances the ability to cope with challenging situations and balances emotions. Objective: To analyze the literature on meditation as a resource for the mental health care of healthcare workers. Methods: This is an integrative literature review of articles from the Virtual Health Library (VHL) database. The search strategy in Portuguese was: (meditação) AND (pessoal de saúde) OR (profissionais da saúde) AND (saúde mental). For searches in English, the terms were translated. Primary articles published between 2019 and 2024, available in full text, and written in Portuguese and English were included. Results: Mindfulness-based interventions have demonstrated positive effects in reducing stress and burnout among healthcare professionals, improving their quality of life and job satisfaction. Programs that combine meditation, yoga, and mindfulness training have proven effective, especially during the COVID-19 pandemic, alleviating emotional exhaustion and promoting self-compassion. Furthermore, approaches such as FIRECARE and online EFT practice have shown significant benefits, highlighting the importance of integrating different methods to maximize mental health outcomes for professionals. Conclusion: Mindfulness techniques have proven effective in reducing stress and burnout when combined with approaches such as positive psychology. It is recommended that healthcare institutions implement mindfulness programs as a promotion of worker health.